Endothelial Progenitor Cells Enter the Aging Arena - Williamson, Kate; Stringer, Sally; Alexander, Yvonne (Frontiers in Physiology, 2012)
Age is a significant risk factor for the development of vascular diseases, such as atherosclerosis. Although pharmacological treatments, including statins and anti-hypertensive drugs, have improved the prognosis for patients with cardiovascular disease, it remains a leading cause of mortality in those aged 65 years and over. Furthermore, given the increased life expectancy of the population in developed countries, there is a clear need for alternative treatment strategies. Consequently, the relationship between aging and progenitor cell-mediated repair is of great interest. Endothelial progenitor cells (EPCs) play an integral role in the cellular repair mechanisms for endothelial regeneration and maintenance. However, EPCs are subject to age-associated changes that diminish their number in circulation and function, thereby enhancing vascular disease risk. A great deal of research is aimed at developing strategies to harness the regenerative capacity of these cells. In this review, we discuss the current understanding of the cells termed “EPCs,” examine the impact of age on EPC-mediated repair and identify therapeutic targets with potential for attenuating the age-related decline in vascular health via beneficial actions on EPCs.